Identifikasi Kerusakan Mobil Menggunakan Sistem Pakar Berbasis Metode Forward Chaining Pada Global Motor Gorontalo - utiarahman, Siti andini (JSAI (Journal Scientific and Applied Informatics), 2020)
Checking and diagnoses of car damage done manually cause the old car working time so that customer satisfaction decreases. To save time from technicians, an application that can help the technician to diagnose damage to his car is required. For that, it can be applied to expert system applications. The expert system as a program enabled to mimic human experts should be able to do things that an expert can do. This app is designed to do diagnose damage to Daihatsu cars. The method used is a descriptive method, which is research that seeks to solve existing problems systematically based on data-existing data, design by using data flow diagrams (DFD), interface form designing Users of the proposed system using the PHP programming language, the database uses Mysql. The result of this research is the expert system used can to provide useful information in assisting in decision making to diagnose car damage.